Особенности разработки термостабилизированных германиевых фотодиодов - Ryuhtin, V. V.; Dobrovolsky, Yu. G. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
The specific aspects of designing germanium avalanche and non-avalanche threshold photodiodes for use in optical radiation testers of fiber-optic communication systems are discussed. It is shown that the application of epitaxial structures and thermoelectric cooling makes it possible to increase the current monochromatic sensitivity of avalanche photodiodes by a factor of 2–3 and reduce the dark current of conventional germanium photodiodes by an order of magnitude.